Identification of halogenated polycyclic aromatic hydrocarbons in biological samples from Alberta Oil-Sands Region. (January 2019) - Xia, Zhe; Idowu, Ifeoluwa; Marvin, Chris; Thomas, Philippe J.; Johnson, Wesley; Francisco, Olga; Stetefeld, Jorg; Crimmins, Bernard; Fry, Mark; Tomy, Gregg T.
Abstract: Halogenated polycyclic aromatic hydrocarbons (HPAHs) were identified in biological samples from the Alberta Oil-Sands Region (AOSR) using gas chromatography coupled with high-resolution time-of-flight mass spectrometry (GC-HRTOF-MS) at a resolving power of 25, 000. Knowledge of the electron ionization (EI) fragmentation behavior of individual HPAH isomers, achieved by injecting authentic standards in full-scan MS mode, was paramount in identifying a suite of HPAHs in samples from the AOSR. Confirmation of compounds in biological samples was based on the measured mass accuracy (±3 ppm) of 2 characteristic ions prominent in the EI mass spectra of each compound. Numerous compounds were detected in the high resolution total ion chromatogram in liver extracts of 4 biological species from the AOSR: river otter ( Lontra Canadensis ), northern pike ( Esox lucius ), lake whitefish ( Coregonus clupeaformis ) and snails ( Gastropod sp.) many of which remain unidentified. Careful examination of the high-resolution accurate mass data suggests that dichloro-anthracene/phenanthrene, bromo-anthracene/phenanthrene and dibromo-fluorene were present in the biological samples. Lipid corrected concentrations of dichloro-PAHs were estimated to be 16.3 ± 11.4 ( n = 4 ) and 5.5 ( n = 1 ) ng/g in lake whitefish and river otter, respectively. Concentrations of mono-bromo-PAHs were an order of magnitude greater in snails (170.5 ng/g) than in northern pike (12.5 ng/g) while concentrations of dibromo-PAHs were 4 times greater in snails than in northern pike. The detection of these compounds in biota implies that these compounds are bioaccumulative. The liver-based biomagnification factor of the dichloro-PAH congener in the river otter/lake whitefish feeding relationship is much smaller than 1 implying that this compound does not biomagnify. Highlights: GC-HR-TOF/MS method was used to identify halogenated compounds in biota. Three halogenated compounds were positively identified in biological samples. These compounds bioaccumulate in biota from the Alberta Oil Sands Region.